Evaluación de la implementación del equipo de Coiled Tubing para operaciones de abandono técnico en pozos con presencia de presión contenida en el Campo Casabe (2021)
This document sets out, as its main objective, the implementation of the Coiled Tubing equipment to carry out technical abandonments in wells with the presence of contained pressure, because this equipment has a wide variety of uses such as drilling, completion, hole reconditioning, of abandonment of the well, among others. In turn, it has a preventive system called Stripper, which generates a dynamic seal that allows the pipe to enter the well and perform work in flowing wells, controlling and containing the pressure, thanks to the fact that it supports up to 10,000 psi, increasing safety and reducing possible incidents during operations.